A High Performance Deep Blue Organic Laser Gain Material. Issue 8 (20th February 2017) - Wei, Qi; Li, Yan; Liu, Jingguan; Fang, Qiyun; Li, Jiewei; Yan, Xiaohong; Xie, Linghai; Qian, Yan; Xia, Ruidong; Huang, Wei
Abstract : High performance organic lasers with both good optical lasing property and desirable carrier mobility still remains a big challenge for realizing electrically pumped organic lasing. In this work, we have developed a carbazole‐end‐capped ladder‐type oligo‐(p‐phenylene) based hybrid oligomer as solution‐processable deep blue laser gain media to reach a good balance between optical property and carrier transporting ability, by introducing moderate steric hindrance into the pi‐conjugated planar oligo‐(p‐phenylene) backbone. This material demonstrates excellent laser performance and moderate hole mobility of 1 × 10 –3 cm 2 V −1 s −1 . The 1‐D distributed feedback (DFB) laser exhibits very low lasing threshold of 0.6 nJ pulse −1 and high slope efficiency of 5.9 ± 0.3% (50% fill factor). More importantly, the prominent ASE performance maintained at very thin film samples. The amplified spontaneous emission (ASE) threshold remains very low (16 nJ pulse −1 ) in the 45 nm‐thickness film. These results might indicate possibilities for electrically pumped gain materials. Abstract : The carbazole‐end‐capped ladder‐type oligo‐( p ‐phenylene) DCz‐LPh5 is demonstrated as an excellent optical gain medium for low‐threshold (0.6 nJ pulse −1 ) deep blue distributed feedback lasers. Moreover, hole mobility is determined as 10 −3 cm 2 V −1 s −1 using the space‐charge limited current method. Notably, a very low amplified spontaneous emission threshold is maintained in very thin films (16 nJ pulse −1 with 45 nm thickness).